How to become the preferred client of your supplier. Issue 2 (13th February 2017) - Poissonnier, Hugues
Abstract : Purpose: This paper aims to show that becoming the preferred client of your supplier can be very useful and giving ideas to help doing so. Design/methodology/approach: This study uses a historical approach. Findings: Propositions for choosing modalities of collaboration with suppliers were studied. Research limitations/implications: Based on Herzberg's theory, suggestions are given to readers. Originality/value: This paper shows that to improve value creation potential, buyers have to make their companies become the preferred client of their suppliers. It is a key question to benefit from all the value creation capacity of these suppliers.